SIKAP GURU TERHADAP ANAK YANG BERKEBUTUHAN KHUSUS DI SD IT ANAK SHOLEH MATARAM - Radiusman Radiusman; Iva Nurmawanti; Setiani Novitasari; Linda Feni Haryati; Maslina Simanjuntak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
The attitude of teachers towards children with special needs is of particular concern to the current government. This is because children with special needs have the same rights as normal children. Teachers are seen as people who have an important role to implement inclusive education inside and outside the classroom. The success of learning for children with special needs in the classroom is supported by positive behavior/attitudes of teachers and the environment during learning activities in the classroom and outside the classroom. This research is a type of qualitative research. This research takes data through the results of interviews with Sholeh IT elementary school teachers. This article will explain how the attitudes of teachers in SD IT Anak Sholeh Mataram with special needs who have learning disabilities and factors that must be possessed by teachers in educating children with special needs who have learning disabilities and how different treatments/attitudes of teachers. Towards children with special needs. and normal children during the learning process. This research is a qualitative study in which data is obtained from interviews with classroom teachers who teach in classrooms where children with special needs experience learning delays. The results of this study are through the patience of teachers and good communication with parents to make changes in attitude for the better than the research subjects.